STRATEGI PENGEMBANGAN KOMPETENSI PEGAWAI BADAN PUSAT STATISTIK KABUPATEN KARAWANG DALAM MENGHADAPI TRANSFORMASI DIGITAL - Gista Septiyanti; Wanta Wanta; Dwi Epty Hidayaty (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
The rapid digital transformation requires the Central Statistics Agency of Karawang Regency to improve employee competence. However, the gap in abilities due to differences in educational backgrounds is a major challenge. The purpose of this study is to analyze the strategies applied in employee competency development, the challenges faced, and the steps needed in dealing with digital transformation. The research approach used is qualitative descriptive, with data collection techniques including interviews, observations, and documentation. Data validation was carried out using source triangulation based on the results of interviews with informants. The results of the study revealed that the Central Statistics Agency of Karawang Regency implemented an effective strategy, including special training according to needs, independent training, mentoring and socialization. The challenges faced are difficulties in adapting to senior employees and differences in educational backgrounds, which require support through socialization, ongoing training and mentoring. The recommended steps include improving technology infrastructure, providing freedom for independent competency development, and strengthening collaboration between divisions. This research provides an important implication that the successful implementation of digital transformation at the Central Statistics Agency of Karawang Regency requires relevant support and training.